Society and Conflict - Pavlović, Nikola R. (Sociološki pregled, 2019)
The text is a critical review of the book by Srđan and Marica Šljukić, authors who point out that the contribution of sociology and sociologists in conflict resolution is rather underestimated and reduced only to the notion of Marx’s class struggle. It is this neglect of sociological insights into conflicts that has led the authors to devote part of their scientific activity to this topic. In their study, the authors presented the ideas of a significant part of thinkers, most of which do not belong to the mainstream of sociology, but also investigated certain social conflicts in ways that were available to them in the given circumstances.